2013
DOI: 10.1007/s00125-012-2814-8
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone deficiency prevents high-fat-feeding-induced hyperglycaemia and adipocyte dysfunction in mice

Abstract: Aims/hypothesis Obesity is associated with aldosterone excess, hypertension and the metabolic syndrome, but the relative contribution of aldosterone to obesity-related complications is debated. We previously demonstrated that aldosterone impairs insulin secretion, and that genetic aldosterone deficiency increases glucose-stimulated insulin secretion in vivo. We hypothesised that elimination of endogenous aldosterone would prevent obesity-induced insulin resistance and hyperglycaemia. Methods Wild-type and al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 53 publications
0
23
0
Order By: Relevance
“…In high fat-, fructose-fed, and genetic models of obesity, MR antagonism ameliorates fatty liver disease with reduction in histologic injury and hepatic triglyceride content (98–100). we similarly observed that aldosterone synthase deficiency ameliorates high fat diet-induced fatty liver histology and hepatic triglyceride content (90). On the other hand, one study found no effect of adrenalectomy or MR antagonism on fatty liver severity (101).…”
Section: Links Between Aldosterone Glucose Tolerance and Insulinmentioning
confidence: 77%
See 1 more Smart Citation
“…In high fat-, fructose-fed, and genetic models of obesity, MR antagonism ameliorates fatty liver disease with reduction in histologic injury and hepatic triglyceride content (98–100). we similarly observed that aldosterone synthase deficiency ameliorates high fat diet-induced fatty liver histology and hepatic triglyceride content (90). On the other hand, one study found no effect of adrenalectomy or MR antagonism on fatty liver severity (101).…”
Section: Links Between Aldosterone Glucose Tolerance and Insulinmentioning
confidence: 77%
“…Some studies argue against a direct adipose tissue affect, however, because aldosterone only impaired insulin signaling at concentrations which activate the glucocorticoid receptor (89). In the setting of diet-induced obesity, genetic aldosterone deficiency reduced adipocyte inflammation and increased circulating adiponectin, although this did not prevent development of obesity or insulin resistance, suggesting that mineralocorticoids other than aldosterone may contribute to insulin resistance in vivo (90). …”
Section: Links Between Aldosterone Glucose Tolerance and Insulinmentioning
confidence: 99%
“…These surprising findings suggested that aldosterone modulates insulin secretion via ROS production, but yet independently of MR [53]. More recently, the same group demonstrated that AS KO mice were relatively protected against HFD-induced beta cell dysfunction, hepatic steatosis, suggesting that aldosterone could be involved in the development of these obesity-associated diseases [54]. Thus, aldosterone could alter insulin secretion through hypokaliemia, induction of islet inflammation or oxidative stress.…”
Section: Aldosterone and Insulin Secretionmentioning
confidence: 90%
“…However, weight gain was unchanged and fasting insulin was highest in the aldosterone synthase knockout mice on the high-fat diet (Luo et al 2013). This suggests involvement of aldosterone in some but not all of the adipose tissue dysfunction related to insulin resistance associated with obesity.…”
Section: Inhibitorsmentioning
confidence: 95%